He effectivness and expedicency of the International Court of Justice interim measures - Bjelica-Vlajić Iris N. (Војно дело)
The two most recent proceedings initiated before the International Court of Justice, regarding local conflicts in which a large number of civilian victims were recorded, once again raised the question of the expediency and effectiveness of this Court's provisional measures and drew attention to its previous practice. The first proceeding was initiated by Ukraine against the Russian Federation, while the second request to initiate the proceeding against Israel in relation to the Palestinians in the Gaza Strip was submitted by the Republic of South Africa. Along with both requests for the initiation of proceedings, provisional measures were requested, in accordance with the Statute and Rules of Procedure of the Court, in the first case to end the armed actions, and in the second, to protect the rights of the civilian population from further, severe and irreparable damage, and ensure compliance with obligations from the Convention on the Prevention and Punishment of the Crime of Genocide (Genocide Convention). States signatories to the Genocide Convention have an obligation not to participate in genocide, and to prevent and punish the perpetrators of genocide. The aim of this work is to present the jurisdiction of the Court, the importance and the course of the procedure, in order to explain the way of specifying provisional measures and the possibilities available to the Court in terms of their execution, as well as the obligations of states and United Nations bodies in relation to the provisional measures in order to demonstrate their effectiveness. The method of content analysis and the historical method, as well as the deduction method were used in the preparation of the paper. The result of the research shows that the International Court of Justice has the authority to order the parties to the dispute to undertake or refrain from undertaking certain activities, and that the successful implementation of the measures largely depends on the support provided by the Security Council and the United Nations General Assembly to the provisional measures of that Court.